THE INCREDIBLE JOURNEY OF A MICROALGAE: A DANCE WITH NUTRIENTS FOR EXCEPTIONAL GROWTH - Hernández Márquez, Sandra Karina; Pérez Sánchez, Rosa Veronica; Nuñez Rodriguez, Edgar; Sosa Olivier, José Aurelio; Hernández Barajas, José Roberto; Laines Canepa, José Ramón (Kuxulkab’, 2024)
In the kingdom of microalgae, “Nannochloropsis oculata” stands out for its adaptability to various diets. Its growth in airlift photobioreactors and various culture media has been explored. The objective was to analyze this growth in controlled environments, using four nutritional recipes. In addition to growth, indicators such as turbidity, apparent color, and suspended solids were monitored, ensuring precise control. Exciting results emerged; this study reveals the relationship of “N. oculata” with nutrients. Findings that uncover mysteries of microalgae cultivation and promise a green future. This incredible journey anticipates more microscopic wonders.